Exploring the rising death rates among older US citizens with heart failure and sepsis: Need for health-care policy reform - Abdul Ahad; Eeshal Fatima; Adeena Jamil; Obaid Ur Rehman; Irfan Ullah; Raheel Ahmed; Bernardo Cortese; Michael E. Hall; Mamas A. Mamas (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Heart failure (HF) patients, often multimorbid and immunocompromised, are particularly vulnerable to sepsis, which increases their risk for mortality. It is therefore crucial to understand the mortality patterns in older adults (≥65) with HF and sepsis for improving care strategies in the United States. Methods: A cross-sectional evaluation of death certificates from the Centers for Disease Control and Prevention's Wide-Ranging Online Data for Epidemiologic Research (CDC WONDER) was conducted to examine HF and sepsis mortality trends. For demographic and geographic subgroups, age-adjusted mortality rates (AAMR) per 100,000 older individuals, alongside annual percent change (APC) in AAMR with 95 % confidence intervals (CI), were derived. Results: Throughout 1999 to 2019, 250,115 deaths associated with HF and sepsis were recorded among older adults, the majority being reported in medical facilities. The overall AAMR escalated from 28.8 in 1999 to 33.7 in 2019. AAMRs were more pronounced in men (33.9) than in women (25.5). Non-Hispanic (NH) Black/African American individuals exhibited the highest AAMRs (42.4). At the same time, NH Asian/Pacific Islanders reported the lowest (18.9). AAMRs were higher in non-metropolitan areas (31.4) and the Southern region (31.1). State-level disparities revealed the highest AAMRs in Mississippi (45.4) and the lowest in Arizona (12.1). Conclusion: Mortality from HF and sepsis has increased over the last 20 years, with NH Black/African individuals demonstrating the greatest increases. Future studies should investigate the mechanisms underlying this increase, particularly focusing on the factors that drive disparities, to develop targeted interventions for vulnerable groups.